A Psychometric Evaluation of the Body Checking and Avoidance Questionnaire Among Brazilian Adults - da Silva, Wanderson Roberto [UNESP]; Neves, Angela Nogueira; Marôco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (Springer Nature, 2021)
Frequent body checking and avoidance are commonly related to psychopathologies; therefore, these behaviors are important to be investigated with appropriate measures. In this study, we investigated the factorial model for Body Checking and Avoidance Questionnaire (BCAQ) and used the structure with the best fit to the data to verify the frequency of body checking and avoidance among adult Brazilian respondents. A total of 1455 individuals completed both the BCAQ and a sociodemographic questionnaire. We evaluated this instrument through factorial, convergent, and discriminant validity, and we determined its reliability. Confirmatory factor analysis revealed that the one-factor model did not fit our data for either female or male samples. Thus, an exploratory factor analysis was conducted, which uncovered the presence of five factors. This model had a good fit to data and was invariant across independent subsamples, but not across sexes. A model with five first-order factors and one second-order factor also had a good fit to data; therefore, its use is recommended to provide a general score for body checking and avoidance behaviors. The general BCAQ score showed a low frequency of body checking and avoidance behaviors among the participants. The BCAQ can gather important data of clinical and epidemiological benefit in the prevention of the psychopathologies, such as eating and obsessive–compulsive disorders.
Keywords: Avoidance; Body checking; Psychometrics; Questionnaire